ChemInform Abstract: Processing of Non‐ferromagnetic Materials in Strong Static Magnetic Field. Issue 7 (29th January 2015) - Sun, Z. H. I.; Guo, M.; Vleugels, J.; Van der Biest, O.; Blanpain, B.
Abstract Review: 52 refs.